2021
DOI: 10.3390/ijms222011147
|View full text |Cite
|
Sign up to set email alerts
|

CHIR99021, trough GSK-3β Targeting, Reduces Epithelioid Sarcoma Cell Proliferation by Activating Mitotic Catastrophe and Autophagy

Abstract: Epithelioid sarcoma (ES) is a rare disease representing <1% of soft tissue sarcomas. Current therapies are based on anthracycline alone or in combination with ifosfamide or other cytotoxic drugs. ES is still characterized by a poor prognosis with high rates of recurrence. Indeed, for years, ES survival rates have remained stagnant, suggesting that conventional treatments should be revised and improved. New therapeutic approaches are focused to target the key regulators of signaling pathways, the causative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…ER stress is also known to induce GSK-3β activation and phosphorylate ULK1 leading to induction of autophagy [91]. On the other hand, several studies have also shown that inhibition of GSK-3β upregulates autophagy flux [11,12]. Moreover, GSK-3β can be also regulated by PKC and elF4A3 to trigger TFEB nuclear localization and activation [65,66].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ER stress is also known to induce GSK-3β activation and phosphorylate ULK1 leading to induction of autophagy [91]. On the other hand, several studies have also shown that inhibition of GSK-3β upregulates autophagy flux [11,12]. Moreover, GSK-3β can be also regulated by PKC and elF4A3 to trigger TFEB nuclear localization and activation [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…TSC2, a GTPase-activating protein (GAP), regulates mTORC1 through Rheb, which converts Rheb-guanosine triphosphate (GTP) into Rheb-guanosine diphosphate (GDP) form to inactivate Rheb, leading to mTORC1 inactivation [97,98]. The inhibition of GSK-3 α/β using the CHIR99021 GSK-3 α/β inhibitor was shown to enhance the ratio of LC3 A/B-II to LC3 A/B-I and effectively decrease p62 expression in epithelioid sarcoma cells [11], suggesting that induction of autophagy occurs in epithelioid sarcoma cells [11]. Moreover, this study also examined the mTORC1 expression and found downregulation of mTOR and p-mTOR expression in CHIR99021 GSK-3 α/β inhibitor treatment [11].…”
Section: Gsk-3-mediated Regulation Of the Mtorc1 Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…CHIR99021, an ATP-competitive inhibitor, has been well established as a selective and potent inhibitor of GSK3 activity [19]. Due to the mechanism of action, to determine if CHIR99021 was in fact targeting and inhibiting GSK3 in our mast cell model, we investigated GSK3 kinase activity by measuring total protein levels of the downstream target β-catenin.…”
Section: Gsk3 Inhibition Via Chir99021 Treatment Impairs Early-phase ...mentioning
confidence: 99%